Akhlak Mulia dalam Pandangan Masyarakat - Mustopa, Mustopa (NADWA, 2014)
This paper elaborate on views of the community on a noble character. Categori-zation of noble character is different in view of the public. This study used a qualitative approach which is the data derived from the literature and society. The results of this study indicate that the noble character in view of the public looks through oral and actions and it is always behaved by someone, and it is not temporary. Normative morality is embedded in the inner nature of the soul that gives rise to act with ease. Morals reflected in a person in relation to God and the community. It was influenced by heredity, environment, and both formal and non-formal education. Individually, moral goodness cause calmness and serenity in a person and make it easier to interact socially with the community.